Identification of a Novel Synthetic Cathinone CMMP - HE Si-yang; DENG Qian-ya; ZHENG Shui-qing; NI Chun-fang; SUN Wen-juan; CAO Fang-qi; LIANG Chen; GONG Fei-jun (Fayixue Zazhi)
ObjectiveTo establish a method to identify an unknown substance based on the combined use of gas chromatography-quadrupole time-of-flight mass spectrometry （GC-QTOF-MS）, ultra-high performance liquid chromatography-quadrupole/electrostatic field orbitrap high resolution mass spectrometry （UPLC-Q/Orbitrap HRMS）and nuclear magnetic resonance （NMR） techniques.MethodsThe unknown substance was dissolved in methanol and was detected by GC-QTOF-MS and UPLC-Q/Orbitrap HRMS, and was dissolved in methanol-d4 to be detected by NMR.ResultsThe main characteristics ion peaks of components with retention time of 9.67 min in GC-QTOF-MS measured were 84.080 8, 110.999 7, 128.107 0 （base peak）, 138.994 7, etc. The protonated molecular ion peak m/z in UPLC-Q/Orbitrap HRMS was 268.109 3. It was inferred that the unknown substance was an analog of the synthetic cathinone substance 2-methyl-1-[4-（methylthio）phenyl]-2-morpholinopropan-1-one （MTMP） by comparing the mass spectrum information and molecular structure of MTMP. NMR analysis confirmed it as a novel N-morpholine substituted synthetic cathinone substance 1-（4-chlorophenyl）-2-methyl-2-morpholinopropan-1-one （CMMP）.ConclusionThe method established in this study can be used for structural confirmation of CMMP.